Seasonal variability of groundwater level effects on the growth of Carex cinerascens in lake wetlands. Issue 1 (17th December 2019) - Feng, Wenjuan; Mariotte, Pierre; Xu, Ligang; Buttler, Alexandre; Bragazza, Luca; Jiang, Jiahu; Santonja, Mathieu
Abstract: Groundwater level is crucial for wetland plant growth and reproduction, but the extent of its effect on plant growth can vary along with changed precipitation and temperature at different seasons. In this context, we investigated the effect of two groundwater levels (10 cm vs. 20 cm depth) on growth and reproductive parameters of Carex cinerascens, a dominant plant species in the Poyang Lake wetland, during three seasons (spring, summer, and autumn) and during two consecutive years (2015 and 2016). Carex cinerascens showed low stem number, height,  and individual and population biomass in summer compared to spring and autumn. 10 cm groundwater level was overall more suitable for plant growth resulting in higher stem height and biomass. However, the interactive effect between groundwater level and season clearly demonstrated that the effect of groundwater level on plant growth occurred mainly in autumn. After the withering of the plant population in summer, we observed that C. cinerascens growth recovered in autumn to similar values observed in spring only with 10 cm groundwater level. Consequently, we could deduce that lowering groundwater level in the studied Poyang Lake wetland will negatively impact C. cinerascens regeneration and growth particularly during the second growth cycle occurring in autumn. Additionally, our results showed that, independently of the season and groundwater level, population biomass of C. cinerascens was lower during drier year. Altogether, our findings suggest that water limitation due to both reduction in precipitation and decreased groundwater level during the year can strongly impact plant communities. Abstract : We investigated the effect of groundwater level on growth and reproductive parameters of Carex cinerascens, a dominant plant species in the Poyang Lake wetland, during two consecutive years. We clearly demonstrated that the effects of groundwater level on plant growth occur mainly in autumn.